A Thermodynamic Model for Time Dependent Billiards - Leonel, Edson Denis [UNESP] (My University, 2021)
This chapter is dedicated to discuss some thermodynamic properties for a set of particles moving confined to a time dependent oval billiard. Two approaches are considered. One of them uses the heat transfer, well described by the Fourier equation, leading to an analytical expression for the temperature. The other one involves the time evolution of an ensemble of different initial conditions for a time dependent billiard dynamics. The temperature of the gas of particles is obtained from a connection with the equipartition theorem.